Odpowiedzi

2009-10-11T17:19:11+02:00
Funkcja wykładnicza ma wzór y=a^x
a)P(-2,9)
9=a⁻²
3²=a⁻²
3²=1/(a²) /*(a/3)²
a²=(1/3)²
a = 1/3
zatem funkcja ma wzór y=(1/3)^x


a)P(-3,125)
y=a^x
125=a⁻³
5³=a⁻³
a=1/5
Wzór funkcji: y=(1/5)^x


b1) y=loga(x)
gdzie a jest podstawą logarytmu, a≠1 i a>0, Da=(0,1)∨(1,∞)
P(9,-6)
-6=loga(9)
a⁻⁶=9
1/(a⁶)=3² /*(a⁶/3²)
a⁶=(1/3)²
a=(1/3)^(1/3)∈Da
wzór funkcji y=log∛⅓(x)

b2)y=loga(x)
Da=(0,1)∨(1,∞)
P(16,-6)
-6=loga(16)
a⁻⁶=2⁴
a=(1/2)^(2/3)∈Da
wzór funkcji: y=log[(½)^(⅔)](x)
2009-10-11T19:09:44+02:00
Funkcja wykładnicza ma wzór y=a^x
a)P(-2,9)
9=a⁻²
3²=a⁻²
3²=1/(a²) /*(a/3)²
a²=(1/3)²
a = 1/3
zatem funkcja ma wzór y=(1/3)^x


a)P(-3,125)
y=a^x
125=a⁻³
5³=a⁻³
a=1/5
Wzór funkcji: y=(1/5)^x


b1) y=loga(x)
gdzie a jest podstawą logarytmu, a≠1 i a>0, Da=(0,1)∨(1,∞)
P(9,-6)
-6=loga(9)
a⁻⁶=9
1/(a⁶)=3² /*(a⁶/3²)
a⁶=(1/3)²
a=(1/3)^(1/3)∈Da
wzór funkcji y=log∛⅓(x)

b2)y=loga(x)
Da=(0,1)∨(1,∞)
P(16,-6)
-6=loga(16)
a⁻⁶=2⁴
a=(1/2)^(2/3)∈Da
wzór funkcji: y=log[(½)^(⅔)](x)